Curing Cognitive Hiccups: A Defense of The Extended Mind - Clark, Andy (My University, 2007)
Human cognitive processing, according to the Extended Mind Hypothesis may at times extend into the environment surrounding the organism. Such a view should be contrasted with a nearby, (but much more conservative) view according to which certain cognitive processes lean heavily on environmental structures and scaffoldings, but do not thereby include those structures and scaffoldings themselves. This more conservative view may be claimed to capture all that can be of philosophical or scientific interest in such cases, and to avoid some significant dangers into the bargain. I shall argue, by contrast, that (in the relevant cases) it is the conservative view that threatens to obscure much that is of value, and that a robust notion of cognitive extension thus earns its keep as part of the emerging picture of the active embodied mind. To make this case I first sketch some quite general responses to the worries that motivate the more conservative view. I then present some new examples and arguments that aim to flesh out the skeleton responses and to further illuminate the nature and importance of cognitive extension itself.
To appear in the Journal of Philosophy 2007
Keywords: Extended Mind Hypothesis; Philosophy